Amelanotic Malignant Melanoma of the Male Urethra: A Potential Diagnostic Pitfall. (August 2020) - Caputo, Alessandro; Califano, Alfonso; Fabiano, Marco; Altieri, Vincenzo; Zeppa, Pio; D'Antonio, Antonio
A rare disease in an unusual site can closely mimic a typical presentation of a common disease, sometimes with devastating consequences. We present a case of primary amelanotic malignant melanoma of the urethra in a male, with clinical and histological characteristics that could have led to a mistaken diagnosis of high-grade urothelial carcinoma. Amelanotic mucosal melanoma should be suspected in all cases of high-grade mucosal tumors with practically any appearance (epithelioid, sarcomatoid, anaplastic, mixed). Morphological hints pointing toward melanoma—such as the presence of sparse melanin pigment or melanoma in situ—should be sought, and if absent, an immunohistochemical panel comprising S100 and HMB45 should be performed.